Physical, Morphological, Tensile, and Thermal Stability Characteristics of Novel Tinospora Cordifolia Natural Fiber - Jamaluddin Hindi; Muralishwara K; K Subrahmanya Bhat; Gurumurthy B M; Ayman Ibrahim; Shivaprakash Y M (Journal of Natural Fibers)
This article presents an analysis on the characterization of the natural fibers from the stem of Tinospora cordifolia plant/vine. Several characterizations/measurements were carried out on the water retted fibers to ascertain their properties. These included diameter and density measurements, X-ray Diffraction (XRD) analysis, chemical composition by gravimetric method, Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) spectroscopy, single fiber tensile tests, and Thermogravimetric analysis (TGA). The fibers had an average diameter of 202 µm and density of 0.6 g/cm3. The SEM images revealed a rough surface which highlights the potential for good adhesion with the polymer matrix. The Crystalline Index (C.I) and Crystallite Size (C.S) obtained from the XRD spectra were 60.19% and 2.56 nm, respectively. Amount of cellulose, hemicellulose, lignin, and extractives in the fiber were 65%, 12%, 17%, and 6%, respectively. FTIR analysis revealed the presence of major constituents of the natural fiber such as cellulose, hemicellulose, and lignin. The tensile strength, Young’s modulus, and percentage elongation at break of the fiber were 484 ± 100 MPa, 22 ± 4 GPa, and 3.8 ± 1%. The onset of thermal degradation (Tonset) and maximum thermal degradation (Tmax) temperatures were 259°C and 368°C, respectively. Mechanical and thermal properties of the fiber were satisfactory when compared with popular natural fibers.